Mortality among workers exposed to asbestos at the shipyard of Genoa, Italy: a 55 years follow-up - Domenico Franco Merlo; Marco Bruzzone; Paolo Bruzzi; Elsa Garrone; Riccardo Puntoni; Lucia Maiorana; Marcello Ceppi (BMC, 2018)
Abstract Background Exposure to asbestos remains a global issue due to its massive use in the twentieth century and its long environmental persistence. Exposure to asbestos still occurs during dismantling of ships and vessels, buildings renovation, mining operations, and is reported in developing countries. Current estimate report exposure of hundreds of million people in occupational settings in countries where its use remains unregulated. Methods We conducted a historical prospective cohort mortality study aimed at estimating mortality from specific causes, the temporal changes of pleural and lung cancer mortality, and the attributable fraction (AF) of lung cancer deaths following asbestos exposure. The study included 3984 shipyard workers employed at the shipyard of Genoa, Italy, between 1960 and 1981 and followed up to December 2014. Standardized Mortality Ratios (SMR) and their 95% confidence intervals (95%CI) were computed. Results Overall deaths recorded were 3331 (83.6%). Excess mortality was observed for all cancers (SMR = 127, 95%CI:120-134), pleural mesothelioma (575, 469-697), cancers of the larynx (183, 134-244) and of the lung (154, 139-170), and for respiratory tract diseases (127, 114-141), including asbestosis (2277, 1525-3270). Ninety out of 399 deaths (22.6%) from lung cancer were attributed to asbestos exposure. The estimated lung cancer AF was 49.3% in workers with the highest SMR for pleural cancer. Median latency times for pleural and lung cancer were 42.8 years (minimum latency: 9.3 years) and 38.7 years (minimum latency: 6 years). The peak of mesothelioma incidence, expected in Italy in the period 2015-2024, was confirmed. Conclusions The long follow-up period of our study allowed the detection of a substantial disease burden following asbestos exposure. These findings support the urgent need for the prevention of asbestos related diseases through the implementation of asbestos ban worldwide, including those countries where asbestos is still mined, manufactured and used.